2010
DOI: 10.1016/j.jsha.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac magnetic resonance with gated SPECT for evaluation of left ventricular function and volumes in patients with severe and multiple myocardial perfusion defects

Abstract: Objectives: Gated SPECT is an accurate technique for assessment of myocardial perfusion (MP), left ventricular ejection fraction (LVEF), end-diastolic volume (EDV) and end-systolic volume (ESV). However recent studies have concluded that there are large discrepancies in assessment of LVEF and volumes by gated SPECT in patients with multiple severe myocardial perfusion defects. We sought to investigate the correlation between LVEF and volumes calculated by gated SPECT and cardiac magnetic resonance (CMR) in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…All contemporary camera-computer systems incorporate software applications capable of quantitative analysis of LVEF and volumes, based on fully automated (and therefore highly reproducible) detection of the border between the myocardium and the blood (Figure 6) [29]. ECG-gated SPECT showed a very good correlation with CMR in the evaluation of LV end-diastolic volume, but not when end-systolic volume and EF were computed [30]. Pros.…”
Section: Nuclear Cardiology Ecg-gated Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
See 1 more Smart Citation
“…All contemporary camera-computer systems incorporate software applications capable of quantitative analysis of LVEF and volumes, based on fully automated (and therefore highly reproducible) detection of the border between the myocardium and the blood (Figure 6) [29]. ECG-gated SPECT showed a very good correlation with CMR in the evaluation of LV end-diastolic volume, but not when end-systolic volume and EF were computed [30]. Pros.…”
Section: Nuclear Cardiology Ecg-gated Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…Values of spatial and temporal resolution for different cardiac imaging techniques. TTE = transthoracic echocardiography, CMR = cardiac magnetic resonance, CT = computed tomography, SPECT = single photon emission computed tomography[27,30,40].…”
mentioning
confidence: 99%
“…Beitner et al 21 reported a very good association between CMR and SPECT scan with an intra-class correlation coefficient (ICC) of 0.89. Fathala et al 22 reported moderate correlation for LVEF measurements between these two techniques in ninety one known CAD patients (r=0.5 and p-value <0.007). Likewise, Bavelaar-Croon et al 23 reported good correlation (r=0.85) between these two methods in twenty one patients.…”
Section: Discussionmentioning
confidence: 97%
“…Other factors that may contribute to the discrepancies between these two modalities include the use of different algorithms and the possibility that in patients with large perfusion defects, severe reduction or absence of photon counts in a myocardial region may lead to an underestimation of regional wall motion, due to inadequate visualization. 11 Using conventional Anger camera with waiting periods after stress tracer injection of at least 15 minutes, but sometimes also up to 60 minutes, post-stress LV function and volumes may be underestimated and early ischemic functional changes after stress test might be not identifiable. In addition, acquisition time with conventional cameras is very long and this may lead to a resolution of the LV function during this long time.…”
mentioning
confidence: 99%